Counseling about Stress Cooping Strategy for Employees - Irmayani, Irmayani; Ginting, Rosita; Br Bangun, Sri Melda; Samura, Jul Asdar Putra; Fadillah, Raja Safriana (JURNAL PENGMAS KESTRA (JPK), 2023)
Every company tries to provide the best service to its customers. Various ways and efforts are made by the company to make it happen. However, not infrequently many companies are not aware that the workload given to their employees is above normal limits which causes employees to experience stress. Job stress occurs because there are sources or work stressors that cause individuals to experience excessive pressure imposed on them due to too many demands, obstacles or opportunities. Employees are required to work faster, more diligently and more tenaciously to achieve the company's business targets. Employee productivity will decrease when employees experience stress. If employees experience stress, it will ultimately damage performance within the company itself. In order for the stress experienced by employees to be well controlled, it is necessary to carry out stress management. Coping is an attempt to deal with a problem experienced by someone. Coping that everyone does will be different. This community service activity aims to explain tips on managing stress that occurs in every employee. PT. Pelita Adi Pratama Tanjung Balai was the target of this community service activity. This activity was carried out in March 2023 with a total of 51 participants. The method of implementing this community service is by providing direct education to employees regarding tips on managing stress through presentation of power points that have been prepared by the team. In carrying out this activity, the participants were very enthusiastic about the delivery of the material provided by the team. It is expected that every company pays attention to the workload given to employees so that worker productivity remains good and when the workload given is excessive, rewards need to be given so that workers remain happy and not stressed even though the burden given is excessive.